S114 Feasibility study for a randomised controlled trial of Pseudomonas aeruginosa eradication treatment in patients with Bronchiectasis. (12th November 2015) - Abo-Leyah, HR; Smith, A; Clark, M; Hill, J; Fardon, TC; Chalmers, JD
Abstract : Introduction: Guidelines recommend Pseudomonas aeruginosa (PA) eradication treatment for new isolation of PA in bronchiectasis patients, but evidence is lacking. We performed a feasibility study to identify how many patients with new PA isolation would be eligible for a future randomised controlled trial (RCT). Methods: For 12 months (2013–2014) we piloted a PA "alert" system that would notify the study team when PA was isolated in sputum samples. Patients were reviewed using electronic medical records to classify patients as 1- New PA, having never isolated PA before and therefore eligible for eradication, 2- Relapsed PA, patients having been free from PA and now isolating it again- therefore eligible for eradication, 3- Chronic PA, and therefore not eligible for eradication, 4- patients without HRCT confirmed bronchiectasis. Anti-PA IgG antibodies were measured in serum as a predictor of potential eradication success. Results: There were 322 PA isolates from sputum over 12 months, in 156 patients. 22 patients presented new PA, 13 patients relapsed PA, 17 chronic PA and 104 patients did not have bronchiectasis (66%). The most frequent diagnoses in the non-bronchiectasis group was COPD. Overall, 35 patients would have been eligible for a trial of PA eradication on clinical grounds. Of these patients, clearance (negative PA culture at next follow-up sample) was demonstrated in 63%. PA IgG was positive in all of the patients with chronic PA, and identified those with successful clearance: sensitivity 93% and specificity 54%. A low antibody level was strongly associated with successful eradication (negative likelihood ratio 0.06, successful eradication in 92.3%). Mortality was very high in this patient group. 9%, 30% and 24% of patients died within 12 months follow-up in the 3 groups respectively. Conclusion: This feasibility demonstrates that a future community based RCT of PA eradication would require a large number of centres, and be resource intensive. Major challenges in powering a future study include the low proportion of true first isolates and the high frequency of spontaneous PA clearance. Raised PA IgG was not sufficiently specific to exclude successful eradication, but a low PA IgG suggests a high likelihood of success.